2006
DOI: 10.1007/s10947-006-0401-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the zirconium local surrounding on ligand substitution in solutions

Abstract: EXAFS and SAXS methods have been used to examine zirconium hydroxide and oxychloride aqueous solutions in the presence of sulfuric acid in a wide range of concentrations, as well as a zirconium sulfate aqueous solution. The structure of the complexes and their transformation regularities were determined. Structures of the given complexes and structures of zirconium hydroxide and zirconium oxychloride and hydroxide complexes in aqueous solutions were compared. Complexes in zirconium hydroxide and oxychloride aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…It reproduces the pre-edge feature as well as the fine structure at the main edge with a very good match in the relative energy positions compared to the experiment. In this ZrO 8 -cluster, the oxygen ligands form an irregular polyhedron with Zr-O distances ranging from 2.110 to 2.338Å (Mak, 1968), which is consistent with the results of Hagfeldt et al (2004) and Kanazhevskii et al (2006).…”
Section: Zirconium In Fluidssupporting
confidence: 89%
See 1 more Smart Citation
“…It reproduces the pre-edge feature as well as the fine structure at the main edge with a very good match in the relative energy positions compared to the experiment. In this ZrO 8 -cluster, the oxygen ligands form an irregular polyhedron with Zr-O distances ranging from 2.110 to 2.338Å (Mak, 1968), which is consistent with the results of Hagfeldt et al (2004) and Kanazhevskii et al (2006).…”
Section: Zirconium In Fluidssupporting
confidence: 89%
“…Armstrongite (CaZrSi 6 O 15 Á 3H 2 O, Kabalov et al, 2000), elpidite (Na 2 ZrSi 6 O 15 Á 3H 2 O, Cannillo et al, 1973), eudialyte (Na 12 Ca 6 Fe 3 Zr 3 Si 24 O 66 (OH) 5 Cl, Golyshov et al, 1972), and wadeite (K 2 ZrSi 3 O 9 , Blinov et al, 1972) represent examples of alkali and alkaline-earth zircono-silicate minerals with Zr in 6-fold coordination. Zirconium is 8-coordinated in ZrOCl 2 Á 8H 2 O, zircon, and the standard solution (5000 ppm Zr) (Mak, 1968;Finger, 1974;Kanazhevskii et al, 2006;Hagfeldt et al, 2004). Seven-fold coordinated Zr is found in monoclinic ZrO 2 (baddeleyite, Smith and Newkirk, 1965).…”
Section: Zirconium Concentrations In Fluidsmentioning
confidence: 96%
“…The strength of the acid sites depends on a series of features such as: metal electronegativity [35], the number of d-electrons [37], the nature of the binder material [23], the intrinsic sulfate group content and the coordination state of oxygen and sulfur in the catalyst. The active surface sites consists in: (1) polysulfate species with mainly three or four S atoms and two ionic bonds of S-O-Zr in addition to S=O coordination bonds with Zr, the active site being Lewis sites on the S atoms [16,38]; (2) a complex mixture of open trimer with zirconium atoms bonded by sulfate groups while bridge sulfate groups form Zr-O-S-O-Zr bonds; and three terminal sulfate groups and three terminal hydroxyl groups for each zirconium atom [39]. Moreover, Yamaguchi [40] concluded that the generation of high acidity was accompanied by the formation of S 6?…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies describe different operating mechanism for sulfated zirconia samples: (i) the active surface sites consists in polysulfate species with mainly three or four S atoms and two ionic bonds of S-O-Zr in addition to S=O coordination bonds with Zr, the active site being Lewis sites on the S atoms [30]; (ii) the active sites are a complex mixture of open trimer with zirconium atoms bonded by sulfate groups while bridge sulfate groups form Zr-O-S-O-Zr bonds; and three terminal sulfate groups and three terminal hydroxyl groups for each zirconium atom [31]. Moreover, Yamaguchi [32] concluded that the generation of high acidity was accompanied by the formation of S 6?…”
Section: Discussionmentioning
confidence: 99%